Mixing characteristics of inclined dense jets with different nozzle geometries - Jiang, Mingtao (2021)
In the present study, we performed a laboratory investigation to examine the mixing characteristics of 45° inclined dense jets from different nozzle geometries using the technique of Planar Laser Induced Fluorescence (PLIF). The geometries included the circular, square and diamond shapes, as well as the duckbill shape of non-return duckbill valves that are now commonly used for brine outfalls and the star shape of non-return star valves that are available commercially but have not been adopted so far. The concentration centrelines, cross-sectional profiles and spread widths were quantified in the experiments. The results showed that the circular, square and diamond nozzle geometries have similar behavior, implying that the differences of their discharge length scale are not sufficiently large to induce a significant effect. On the other hand, the duckbill and star nozzle geometries have relatively higher dilutions both at the centreline peak and return points. Interestingly, the duckbill nozzle has a relatively lower rise height compared to the others, potentially due to the strong influence of axis-switching effect. In addition, we also performed numerical simulations using the Large Eddy Simulations (LES) approach with the Dynamic Smagorinsky sub-grid model for the diamond, duckbill and star shape nozzle geometries in the experiments. The comparison showed that the time-averaged geometrical characteristics from the three different nozzle geometries can be simulated reasonably well before the centreline peak but with slight over-predictions after that. Meanwhile, the dilution characteristics are underestimated by ~25% generally, which are similar to previous LES results with the reference circular nozzle. The spectral density distribution of the concentration fluctuations clearly demonstrated that the production of turbulence energy in the larger eddies is enhanced by the non-circular nozzles, which is also consistent with the increase in dilutions with these nozzles.